2019
DOI: 10.1002/smtd.201900337
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Screening of Single Transition Metal Atoms Embedded in MXene Defects as Superior Electrocatalyst of Nitrogen Reduction Reaction

Abstract: The MXene‐supported single transition metal systems have been reported as promising electrocatalysts for hydrogen evolution reaction (HER) and carbon dioxide reduction reaction. Herein, the potential performance of MXene‐based catalysts was explored on nitrogen reduction reaction (NRR). Density functional theory computations are carried out to screen a series of transition metal atoms confined in a vacancy of MXene nanosheet (Mo2TiC2O2). The results reveal that the Zr, Mo, Hf, Ta, W, Re, and Os supported on de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
169
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 245 publications
(178 citation statements)
references
References 63 publications
(112 reference statements)
3
169
0
Order By: Relevance
“…17) were also developed through selective etching of (Mo 2/3 Sc 1/3 ) 2 AlC and (W 2/3 M 1/3 ) 2 AlC (M ¼ Sc, Y), respectively. Until now, approximately thirty MXene members have been synthesized, 18 which have been demonstrated to show widespread applications, such as energy storage, [19][20][21] electromagnetic shielding, 22 sewage treatment, 23 nuclide adsorption, 24 photothermal therapy, 25 multicolor cellular imaging, 26 electrocatalysts, 27,28 etc.…”
Section: Introductionmentioning
confidence: 99%
“…17) were also developed through selective etching of (Mo 2/3 Sc 1/3 ) 2 AlC and (W 2/3 M 1/3 ) 2 AlC (M ¼ Sc, Y), respectively. Until now, approximately thirty MXene members have been synthesized, 18 which have been demonstrated to show widespread applications, such as energy storage, [19][20][21] electromagnetic shielding, 22 sewage treatment, 23 nuclide adsorption, 24 photothermal therapy, 25 multicolor cellular imaging, 26 electrocatalysts, 27,28 etc.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the activity, since the most severe challenge for aqueous NRR is the poor efficiency ascribed to the competitive HER, the selectivity between HER vs NRR is further considered . Figure (c) presents the adsorption affinity of *N 2 and *H on FeN 3 moiety.…”
Section: Resultsmentioning
confidence: 99%
“…Single atom catalyst is one of the hottest topics in heterogeneous catalysis due to its high atomic utilization and the adjustable reactivity . For the given heteroatoms, the presented substrate leads to the distinct activity . Considering the unique physical/chemical property, the two‐dimension graphene and its derivatives are commonly adopted to hold the transition metal atom .…”
Section: Introductionmentioning
confidence: 99%
“…Single transition metal (TM) atom, such as Mo, Ru, and Au, can effectively improve the electrocatalytic NRR performance of MXene. According to DFT calculations, Li et al [77] systematically studied a series of single TM atoms confined in a vacancy of MXene nanosheet (Mo 2 TiC 2 O 2 ). The results revealed that the Zr, Mo, Hf, Ta, W, Re, and Os supported on the defective Mo 2 TiC 2 O 2 layer could significantly promote the NRR process.…”
Section: Nitrogen Reduction Reactionmentioning
confidence: 99%